Polimerisasi Emulsi Asam Tanat : Pengaruh Inisiator dan Surfaktan Terhadap Efisiensi Dye Sensitized Solar Cell (DSSC) - Susanti, Melly; Hardeli, Hardeli (Periodic, 2019)
Dye sensitized solar cell (DSSC) are photoelectrochemical based solar cells that involve the transfer of electrical charges from one phase to another. This research was carried out aimed at making DSSC (Dye Sensitized Solar Cell), Knowing the value of the conversion of solar energy into electrical energy and determining the value of the resulting efficiency. In this research, TiO2 degusa P-25 is coated with ITO glass by conductive part through doctor blande technique. Photon absorbent substances in this study used dye from tanned acid which was polymerized results characterization with FTIR on dyes has a strong absorption band at 1050 nm wavefroms indicating the presence of ether functional groups. In addition, when the DSSC circuit is illuminated by a 24 watt UV lamp it will produce electrical properties such as resistance and voltage as measured by a digital multimeter. Variation of inisiator and surfactant can influence the efficiency of the DSSC prodyced the highest efficiency is produced at a concentration of 0,5 M inisiator and 16 grams of surfactant mass which is 7,145 %.